Kontruktivisme dalam Perkuliahan Maharah Kalam Menggunakan Media Instagram: Implementasi, Problematika dan Persepsi Mahasiswa di Indonesia - Bahruddin, Uril; Amrullah, Abdul Malik Karim; Audina, Noor Amalina (Institut Agama Islam Negeri Curup, 2021)
This study aimed to explore the speaking skill in lecturing processes using Instagram media based on the constructivism theory, the problems, and students’ perceptions of the lecturing process. This study used a descriptive qualitative approach with several data collection techniques, namely observation, interviews, and questionnaires. The results of this study concluded that in the implementation of speaking skill lectures, the lecturer used several steps, namely: (1) Instagram media preparation, (2) introduction to the topic, (3) and several core stages oriented to emphasizing the construction of students’ thinking in making the concept of speaking. This study also found several problems such as weak internet networks and a lack of confidence amongst students to upload their speaking skill videos on their personal Instagram accounts. Students also gave positive perceptions such as increased thinking skills and an increase in the number of followers of their Instagram accounts. On the other hand, the researchers also found negative perceptions such as their weak scientific capacity in video editing, speaking skill, and gadgets’ conditions that do not support video editing applications. The researchers suggest that further research is conducted on the integration of constructivism theory with several other social media popular among learners.